Cover Image. Issue 6 (24th May 2021) - Soneru, Codruta N.; Fernandez, Allison M.; Bradford, Victoria; Staffa, Steven J.; Raman, Vidya T.; Cravero, Joseph; Zurakowski, David; Meier, Petra M.; ,
Abstract : The cover image is based on the Research Report A survey of the global impact of COVID‐19 on the practice of pediatric anesthesia: A study from the pediatric anesthesia COVID‐19 Collaborative Group by Codruta N. Soneru et al., https://doi.org/10.1111/pan.14174 .